2012
DOI: 10.1002/jae.2290
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐nonparametric Estimation of Consumer Search Costs

Abstract: This paper studies the estimation of the cost of non-sequential search. We provide a new method based on semi-nonparametric (SNP) estimation that allows us to pool price data from different consumer markets with the same underlying search cost distribution but different valuations or selling costs. We show that pooling data from different markets increases the number of estimated critical search cost cutoffs at all quantiles of the search cost distribution, which increases the precision of the estimates. A Mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 48 publications
(90 reference statements)
0
25
0
Order By: Relevance
“…If we now use the same change of variable in the equilibrium profit equation y yields 17 Moraga-Gonzalez et al (2013) show that the model described here is nonparametrically identified if the number of searches does not tend to infinity.…”
Section: The Modelmentioning
confidence: 94%
“…If we now use the same change of variable in the equilibrium profit equation y yields 17 Moraga-Gonzalez et al (2013) show that the model described here is nonparametrically identified if the number of searches does not tend to infinity.…”
Section: The Modelmentioning
confidence: 94%
“…With only data on prices but not on individual consumers, a necessary limitation of our model, and others in the literature on which we build, is that consumer heterogeneity is one‐dimensional. Importantly, as Hong and Shum (), Moraga‐González and Wildenbeest (), and Moraga‐González, Sandor, and Wildenbeest () have shown, even with only the price distribution at hand, identifying features of the search cost distribution is still feasible. This heterogeneity leads consumers to search different numbers of firms to obtain prices, which in turn supports the mixed strategy pricing equilibrium among firms.…”
Section: The Theoretical Modelmentioning
confidence: 99%
“…In this paper, we propose a dynamic model with forward‐looking consumers to estimate the population consumer search cost distribution. Like many other recent studies, such as Hong and Shum (), Moraga‐González and Wildenbeest () (henceforth MGW), Wildenbeest (), Moraga‐González, Sandor, and Wildenbeest (), and Sanches, Silva Junior, and Srisuma (), we focus on the case where only the distribution of prices in each period is observed, but no individual‐level data on consumers is available. We show that if consumers have the option to delay purchase until a later period, a dynamic selection problem exists that will cause estimates obtained from a static model to be biased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sorensen (2000), Lach (2002), Brown and Goolsbee (2002), Barron et al (2004), Lewis (2008), Chandra andTappata (2011), Pennerstorfer et al (2015), and Sherman and Weiss (2015), or ii) structural estimations, e.g. Wildenbeest (2011), Moraga-González et al (2013), Giulietti et al (2014), Allen et al (2014), and An et al (2015). or 'surplus' (Simester (1997), Hosken and Reiffen (2007), Wildenbeest (2011), Dubovik andJanssen (2012), Anderson et al (2015)). However, these papers only use it to compute sales equilibria in specific market settings, and do not use the associated profit function, π(u), to explore any general results or implications.…”
Section: Related Literaturementioning
confidence: 99%